Bridging External Stakeholders and Sustainability Literature: a review looking at a project management context - Santos, Manoela Pastor dos; Raposo, Marcela Melo Rego; Ferreira, Edivan Alexandre; Berssaneti, Fernando Tobal; Salerno, Mario Sergio; Carvalho, Marly Monteiro de (Brazilian Journal of Operations & Production Management, 2023)
Goal: This study aims at bridging the stakeholder and sustainability literature, focusing on the project context. It aims at identifying the main challenges of mapping and dealing with the external stakeholders concerning the sustainability perspective during the project development. Design/Methodology/Approach: The research design is a literature review merging bibliometric and content analysis. The sampling process includes two primary databases, Web of Science and Scopus. We applied the data on the software VoSViewer for the first phase of bibliometric analysis and on software NVivo for better content analysis. Results: This article contributed to the literature with an in-depth analysis of 96 articles that bridge stakeholder and sustainability. It identifies the stakeholder influence on sustainability issues in projects and the main environmental challenges faced. Besides, there is a prominence of the environmental dimension of the triple bottom line; therefore, the social aspect is little considered in stakeholder management projects. Limitations of the investigation: This study presents limitations related to the research methods selected. First, the sampling strategy constrains the sample related to the search strings and logical operators applied. The application of the research’s exclusion criteria brings subjectivity to the analysis. Practical implications: The research highlights the significance of the identification and mapping of the critical stakeholders for alignment of the sustainability strategy for the project development, which helps to explore risks associated with the sustainability aspects. Originality/Value: We contribute by exploring the gap in research in the intersection between stakeholders and sustainability literature in project management.